Empirical correlation operator and many-dimensional Hermite polynomials - Stepakhno, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The action of an empirical correlation operator on the subspaces of vector Hermite polynomials of a given order is studied. The principal part of this operator is selected.